2021
DOI: 10.1111/acer.14609
|View full text |Cite
|
Sign up to set email alerts
|

A cascade of care for alcohol use disorder: Using 2015–2019 National Survey on Drug Use and Health data to identify gaps in past 12‐month care

Abstract: Background Although effective treatments exist, alcohol use disorder (AUD) is undertreated. We used a cascade of care framework to understand gaps in care for persons with AUD. Methods Using 2015–2019 National Survey on Drug Use and Health data, we evaluated the following steps in the cascade of care: (1) adult prevalence of AUD; (2) proportion of adults with AUD who utilized health care in the past 12 months; (3) proportion with AUD screened about their alcohol use; (4) proportion with AUD who received a brie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…The low rates of documented screening contrast with BRFSS and NSDUH data indicating that around 80% of US adults report having been screened for alcohol use by a clinician in the prior 1 to 2 years 13,14 . This difference is likely due in part to the fact that the current study assesses documented screening with a validated screening questionnaire, whereas both BRFSS and NSDUH assess whether patients recall having been asked by a clinician if they drank alcohol.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The low rates of documented screening contrast with BRFSS and NSDUH data indicating that around 80% of US adults report having been screened for alcohol use by a clinician in the prior 1 to 2 years 13,14 . This difference is likely due in part to the fact that the current study assesses documented screening with a validated screening questionnaire, whereas both BRFSS and NSDUH assess whether patients recall having been asked by a clinician if they drank alcohol.…”
Section: Discussionmentioning
confidence: 61%
“…The Centers for Disease Control and Prevention (CDC)'s Behavioral Risk Factor Surveillance System (BRFSS) national survey in 2017 found 81% of patients' self-reported alcohol screening 13 when asked if during a routine checkup within the prior 2 years a medical professional inquired whether they consumed alcohol. Similarly, a recent analysis of the National Survey for Drug Use and Health (NSDUH) data found 76-87% of participants reported being asked about alcohol use by a medical professional in the past year 14 . There are, however, currently relatively few studies examining clinician reports of screening for unhealthy alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a minority received care: 11.6% reported receiving a brief intervention, roughly 5% were referred to treatment, and roughly 6% received treatment. 11 Another study found that primary care physicians underdiagnose patients with alcohol abuse as well as underregister them in medical records. 12 The study reported that of the 179 males and 82 females who met the criteria for AUD via patientreported data, only 1 of the males and none of the females were documented as such by the primary care physician.…”
Section: Underdiagnosed and Undertreatedmentioning
confidence: 99%
“…Despite these negative consequences, and the evidence to support the benefit of AUD related treatment [ 6 , 7 ], less than 20% of individuals with AUD receive psychological/behavioural therapy with or without pharmacotherapy for relapse prevention [ 1 ]. While current statistics are lacking for Canada, a recent study in the United States found that among 21,270 adults with AUD, only 5.8% reported receiving treatment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%